Tracer study of graduate students in guidance and counseling program at the faculty of education in Universitas Riau - Rosmawati, Rosmawati; Donal, Donal (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
Tracer study is one of the studies that need to be done regularly to find out the relevance level between academic programs organized by an educational institution (study program) with the needs on the field, in the end will be a reference to the study program to create competitive advantage through the opinion of the alumni. This research uses a quantitative descriptive method. The Sampling method used purposive sampling method. In this, research will be seen completed the alumni career that includes alumni who go on education, the reason for continuing education alumni, alumni cumulative achievement index, waiting time to work, alumni satisfaction, and suitability between the field of education and employment. Tracer study results produce a number of conclusions and implementation suggestions that are very useful for improving the learning.